The Effectiveness of Curcuma zedoaria Extract in Enhancing Non Spesific Immune Responses of Tiger Grouper (Epinephelus fuscoguttatus) - Agus Putra A. Samad; Eva Ayuzar; Ilhamdi Ilhamdi; Muhammad Hatta (Department of Aquaculture, 2022)
The present study was conducted to determine the effect of using turmeric extract (Curcuma zedoaria) on non specific immune of grouper (Epinephelus fuscoguttatus). During the study, fish were fed a diet containing 0, 0.5, 1.0, 2.5 g extract/kg feed twice a day for 14 days. Observations of non-specific immune parameters such as respiratory burst activity, chemiluminescent response, phagocytic activity, superoxidase dismutase (SOD) and lysozyme activity were sampled at 0, 1, 2, 4, 7 and 14 days. The results showed that fish fed C. zedoaria with 0.5 g/kg feed affected non-specific immune responses, and showed significant effect in the short term. On contrary, for long-term administration causes a decrease and inhibition of non-specific cellular defense activity. Thus, this study concluded that the administration of turmeric extract added to the feed can act as an immunostimulant and increase the non-specific immune response in grouper (E. fuscoguttatus).